Pengabdian Kepada Masyarakat Sosialisasi Dampak LGBT dan Problematikanya di SMP Al-Hikmah Assalafiyyah - Hafizhah, Salwa; Nabila, Salsa; Nurjanah, Syifa; Bariah, Oyoh (Al-Khidmah: Jurnal Pengabdian Kepada Masyarakat, 2025)
The phenomenon of LGBT (Lesbian, Gay, Bisexual, and Transgender) has become an issue affecting the moral and social values of the younger generation, including junior high school students. In addressing the challenges of globalization and the influence of foreign cultures, the "Impact of LGBT and Its Problems" socialization program at SMP Al-Hikmah Assalafiyyah was designed to provide comprehensive education to students. This program aims to enhance understanding of the impacts of LGBT from health, social, psychological, and religious perspectives while instilling moral and Islamic values to shape students' positive character. The activities utilize an educational and participatory approach, involving interactive discussions, simulations, and data-driven material presentations. The primary target is 8th-grade students who are considered vulnerable to social influences. The program results showed an increase in students' understanding of the impacts of LGBT, including health issues such as the transmission of sexually transmitted diseases, social impacts such as the spread of abnormal sexual behaviors, and effects on education and safety. The program also succeeded in encouraging students to think critically and uphold religious and cultural norms in daily life. With high participant enthusiasm, this program is expected to serve as a preventive measure against LGBT influences while strengthening the role of religious education as a foundation for shaping students' morals. This program provides strategic insights for expanding Islamic outreach in educational settings, particularly in creating a young generation with good character and broad insights in accordance with Islamic teachings.